Dinamika Kemurtadan: Kajian Psikologis Terhadap Faktor-Faktor Individu dan Lingkungan dalam Masyarakat Kontemporer - Tamarischa Rante Labi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to explore theological views on apostasy in the context of Christianity. Apostasy is defined as an act of rejection of one's faith and religious teachings, with a focus on serious spiritual consequences. The main source of insight is the Bible, which provides strong warnings against apostasy, highlighting specific passages such as Hebrews 6:4-6. This verse reflects the theological view that for those who consciously abandon the Christian faith, repentance may no longer be possible. This view reflects the serious spiritual consequences that can separate an individual from the presence of God. Although the Bible provides a strong warning against apostasy, the theological perspective also highlights God's grace and forgiveness. The Bible shows that repentance is always open to those who sincerely desire to return to God. In Luke 15:7, Jesus emphasizes the joy in heaven over one sinner who repents, providing hope that despite the seriousness of the apostasy, God always provides a way for repentance and restoration of a spiritual relationship with Him. Overall, the theological view of apostasy reflects a balance between stern warnings about the spiritual consequences and God's gracious mercy that is always open to those who return to Him.